Impact of the International Coffee Agreement on producing countries. - Akiyama, Takamasa (1990)
Briefly describes recent developments in the world coffee market. Uses a global model of the coffee economy to evaluate the effects of the ICA, and to estimate the benefits of the quota system for each producing country. Results of the simulation show that the export quota system had a stabilizing impact on world coffee prices over the period 1981-85.